A rare case of digital myiasis - Carlos Durão; André Barros; Pedro Campos (Elsevier, 2017)
Cutaneous myiasis is the infestation of the skin or mucous membranes by larvae of the order Diptera. Wound myiasis affect the skin with a previous lesion, and it may consume both dead and living tissue. Finger infestation is rarely a cause of death, but it may provoke considerable morbidity. Prompt wound exploration and careful total larvae removal is essential to achieve healing.In the reported case, the patient was presented in an advanced stage of the infestation, with a large area of finger necrosis and amputation, associated with cellulitis extending from the finger's base to the hand. This diagnosis helped uncover a familiar history of severe abuse and neglect.The accurate understanding and management of such injuries are important not only for the orthopaedic treatment but also for the acknowledgment of their social and forensic implications. Keywords: Myiasis, Maggot, Neglect, Mental disorder, Cochliomyia hominivorax